Long-Term Patterns of Bone Mineral Density in an Elite Soccer Player - Milanese, Chiara; Cavedon, Valentina; Corradini, Giuliano; Rusciano, Aiace; Zancanaro, Carlo (Frontiers in Physiology, 2021)
Changes in bone mineral density (BMD) have been associated with association football (soccer) participation. Seasonal changes in BMD of soccer players have been proposed as well. However, previous investigations were based on short-term observations. Actually, longitudinal investigation of BMD in soccer players is lacking, possibly because of frequent inter-club transfer, changes in club policy or continued availability of the relevant facilities. Dual-energy X-ray Absorptiometry-measured areal BMD (aBMD) was obtained during the competitive season in an elite soccer player along ten consecutive years. Findings showed that 1. aBMD tends to increase with age, independently of body mass; 2. The right (preferred, kicking) leg has higher aBMD than the left (non-preferred, support) one; 3. Meaningful (i.e., > least significant change) changes in aBMD take place along the season; 4. The off-season (transition) period has no effect on aBMD. Findings prompt for future research aimed at clarifying the long-term and seasonal patterns of bone characteristics in soccer in relation with age and type/dose of training. Season-around, long-term scrutiny of bone status in soccer players would help controlling for possible changes/asymmetries in bone mineralization/strength.